Impact Of Linguistic Intelligence And Motivation On Arabic Mastery Among Medical Student - Nurdinsyah, Muhammad Maulana; Rohmawaty, Evy Nur; Ritonga, Abdillah Rofiif Fatin; Muchlis, Fauzan (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Arabic language learning at UIN Maulana Malik Ibrahim Malang is part of the Special Arabic Language Development Program (PKPBA), which must be followed by all students, including students of the Medical Study Program. Diverse educational backgrounds and differences in study focus make mastering Arabic a challenge. On the other hand, medical students generally have high cognitive intelligence in a compound manner; in the context of language education, linguistic verbal intelligence is the key, accompanied by high learning enthusiasm as well. This study aims to analyze the effect of verbal linguistic intelligence and learning motivation on medical students' mastery of Arabic. This research uses a mixed-method approach with quantitative data as primary and qualitative data as supporting, collected through observation, interviews, questionnaires, and documentation. Quantitative analysis was conducted with multiple linear regression and partial test (t-test), while qualitative analysis used the Miles and Huberman model. The results showed that partially verbal linguistic intelligence has a significant effect on Arabic language mastery (sig. 0.004), as well as motivation (sig. 0.000). Simultaneously, however, only motivation remained significant (sig. 0.000), while intelligence became insignificant (sig. 0.259), indicating that learning motivation was the dominant factor. Qualitative findings support these results, showing that phonetic and semantic aspects are easier to master, while syntax and praxis still require more attention in the learning process.